Uji Aktivitas Ekstrak Etanol 70% dan Etil Asetat Daun Sukun (Artocarpus altilis (Park.) Fosberg Sebagai Inhibitor Tirosinase. - Herson Cahaya Himawan; Antonius Padua Ratu; Maya Miani (Jurnal Farmamedika (Pharmamedika Journal), 2016)
Melanin is a substance that gives brown or blackish brown on the skin. Tyrosinase is the main enzyme in biosynthesis of melanin. Utilization of breadfruit leaves based chemical compounds therein such as flavonoids and tannins which are derivates of phenol.Then tested of tyrosinase inhibitory activity.The purpose of this study was to determine the power of inhibition of tyrosinase at ethanol extracts 70% and ethyl acetate extracts of leaves of breadfruit. Acquisition of extraction by maceration, subsequently evaporated by means of separation (rotary vacuum evaporator). Maserate were obtained for a each standard series of concentration 2000; 1000; 500; 250; 125; 62,5; 31,25; 15,63 ppm and kojic acid as positive control with concentration 500; 250; 125; 62,5; 31,25; 15,63 ppm, then each sample tested the inhibitory activity of tyrosinase.Based on the results of the study for the highest tyrosinase inhibitory activity shown by ethyl acetate extract of leaves of breadfruit, because it value smaller IC50 than ethanol extracts 70% of leaves ofbreadfruit. The value IC50 the ethyl acetate extract was 245,43 ppm, while the value IC50 the is 3143,21 ppm. However the activity of tyrosinase inhibition of ethanol extracts 70% and ethyl acetate extract of leaves of breadfruit was lower than kojic acid as positive control that has a value IC50 is 19,36 ppm, because the smaller the value IC50 The greater power inhibition of tyrosinase.